Do Good Institutions and Economic Uncertainty Matter to Foreign Direct Investment? - Bommadevara, Ramesh; Sakharkar, Akshay (Asian Economic and Financial Review, 2021)
This study investigates the effects of institutional quality, economic policy uncertainty and other key fundamental factors on foreign direct investment (FDI) inflows for a sample of 22 economies from 2000 to 2019. First, the quality of institutional infrastructure in the host country matter greatly to FDI inflows. Second, a subservient increase in the Economic Policy Uncertainty (EPU) growth rates adversely affects FDI inflows. Additionally, we found that macroeconomic fundamentals pertaining to the level of financial openness, exchange rate stability and financial development in the host country are of great importance to FDI inflows. In essence, the findings from our study suggest that the improvement of macroeconomic fundamentals in conjunction with robust and strong institutional infrastructure can contribute to the moderation of economic policy uncertainty, which deters FDI inflows.